2007
DOI: 10.1177/1545968306298598
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of fMRI Activation in the Perilesional Primary Motor Cortex and Cerebellum With Rehabilitation Training-Related Motor Gains After Stroke: A Pilot Study

Abstract: The evolution of suggestive correlations between serial scans of fMRI adaptive activity within the primary motor cortex and the cerebellum in relation to relevant behavioral changes over the course of 2 weeks of task-specific therapy and then no formal therapy suggests that repeated assessments may be best for monitoring therapy-induced neuroplasticity. This approach may help develop optimal rehabilitation strategies to maximize poststroke motor recovery as well as improve the search for brain-behavior correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
68
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 37 publications
8
68
0
Order By: Relevance
“…However, opposite trends were seen in patients, who showed an increase in task-related activity in these regions following practice, analogous to observations of increased recruitment of task-relevant areas with short-term motor learning for healthy subjects 6,[43][44][45] . The observation of increased brain activation with practice for patients is consistent with previous studies of rehabilitation interventions which have shown that good treatment outcomes are associated with increased activation in brain regions relevant to the task 31,46,47 .…”
Section: Effects Of Motor Practice On Task-related Brain Activitysupporting
confidence: 89%
See 1 more Smart Citation
“…However, opposite trends were seen in patients, who showed an increase in task-related activity in these regions following practice, analogous to observations of increased recruitment of task-relevant areas with short-term motor learning for healthy subjects 6,[43][44][45] . The observation of increased brain activation with practice for patients is consistent with previous studies of rehabilitation interventions which have shown that good treatment outcomes are associated with increased activation in brain regions relevant to the task 31,46,47 .…”
Section: Effects Of Motor Practice On Task-related Brain Activitysupporting
confidence: 89%
“…In addition, with a learning task of the sort used here, there may be inter-individual variation in the effects of a fixed amount of short-term task practise on brain functional responses. While some subjects may have reached a performance plateau, others could continue to improve if allowed to practice for longer (as shown in a previous study of long-term practice effects on brain responses 31 ), and so any associated gains in brain functional responses may not be maximal. Future studies with varied practice schedules, larger groups and a range of motor tasks could test these hypotheses directly.…”
Section: Baseline Differences Between Brain Activity In Patients and mentioning
confidence: 99%
“…Engaging the motor network through training in specific tasks that improves motor learning may increase synaptic efficacy of the distributed motor system, improve motor control, 23 and perhaps enhance the reserve of the motor pathways during repetitive movements. Task-specific training, such as that used for the Spinal Cord Injury Locomotor Trial (SCILT) [24][25][26] and the Extremity Constraint-Induced Therapy Evaluation (EXCITE) trial, 27,28 aimed to optimize identifiable components for learning motor skills.…”
Section: Enhance Motor Learningmentioning
confidence: 99%
“…68 Similarly, repetitive training of the affected arm yielded an increase of activation in the sensorimotor cortex related to hand movements, which initially persisted for weeks after training completion and then decreased in magnitude in relation to the functional gains. 69 Furthermore, a three-week training in chronic stroke patients using robot-assisted training resulted in improvements of hand motor function which was associated with a greater fMRI signal in sensorimotor cortex related to performance of the movements trained by the robot. 70 This increase was task-specific, since it did not occur in relation to non-trained supination/pronation movements with the affected hand and movements of the non-trained hand.…”
Section: The Effect Of Rehabilitative Training and Underlying Neural mentioning
confidence: 99%